Reversible platypnea‐orthodeoxia syndrome induced by rapidly progressive interstitial pneumonia in a patient with polymyositis. Issue 3 (4th June 2014) - Yamakawa, Hideaki; Yoshida, Masahiro; Baba, Yuri; Ishikawa, Takeo; Takagi, Masamichi; Kuwano, Kazuyoshi
Abstract We report a case of platypnea‐orthodeoxia that developed in a 64‐year‐old Japanese woman during an episode of rapidly progressive interstitial pneumonia with polymyositis. Pulmonary infiltrates were predominant in the bilateral lower lobes. The patient was treated successfully with early administration of immunosuppressive therapies and polymyxin B‐immobilized fiber column‐direct hemoperfusion, and her platypnea‐orthodeoxia improved with resolution of the underlying parenchymal lung disease. Reports of platypnea‐orthodeoxia syndrome with interstitial pneumonia are extremely rare. The recognition that platypnea‐orthodeoxia syndrome may occur in multiple disease states, including interstitial pneumonia, is crucial to the understanding of this perplexing disorder.